(3GdfLhe GdTGQbGJ aj PcQ HYV GdUfGjYs - (3GdMSfj GdOeTbj, eMeO Hf CHj GdNjQ ; J b (B10 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj JJe HfYeJg GdUGdMGJ aj PcQ HYV GdUfGFY GdeMJGL EdjgG aj Yde GdejbGJ hQJHJgG Ydi NeSI hYTQjf HGHG ; GdHGH GdChd aj Md GdeUWcG hGdSfOQhS s
(3BNQgG (B:s
(3GdKGdKg JOYc efg TjFG jSjQG HQjbc Ydi GdjO hjJQc MJi jLa hjfaV ZdEf UHZ ecGfg agh eaJhT hEdG adG, GdQGHYI jLYd efg bdjdG aj UajMI fMGS hjLYd Ydi GdfGQ Ch Ydi XgQ LeQI SGYI aEf GMJQb Ch GShO agh eaJhT hEdG ???s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\282s
(3eYLe GdeDdajf (B3\282s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3ejbGJ hadcs